Kemampuan Inkuiri Siswa SMP dalam Pembelajaran IPA Memanfaatkan Media E-LKPD - Thoriq Hasan Andikalan; Supeno Supeno; Iwan Wicaksono (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
This study aims to describe the inquiry ability of junior high school students during science learning using the E-LKPD media. The instrument was E-LKPD media integration of inquiry abilities. Data collection technique in this study uses result of instrument with data analysis technique used is N-Gain test. The results obtained showed the average ability of inquiry at the first meeting was 58.25 to the second meeting with a score of 65.03 then to the third meeting was 76.86. Inquiry ability of each individual also increased, in the first N-gain test students was 71.88% of low criteria, 21.88% of medium criteria, and 6.25% of high criteria. Meanwhile, in the second N-gain test, it was obtained that 53.13% of students had low improvement, 31.25% of students had moderate improvement, and 15.63% of students had high improvement. So it can be concluded that the average inquiry ability of students has increased at each meeting during the learning process by using the E-LKPD media.